2014
DOI: 10.1017/s0967199414000598
|View full text |Cite
|
Sign up to set email alerts
|

The effects of extracellular ATP and its receptor antagonists on pig oocytes during in vitro maturation

Abstract: We measured the ATP concentrations in the porcine follicular fluid derived from three sizes of follicles (small: 6 mm in diameter). Then, the effects of pre-treatment (100 μM each for 30 min before maturation) with antagonists for extracellular ATP receptor P2X or P2Y on the nuclear maturation rate of cumulus-cell-enclosed (COs) or -denuded oocytes (DOs) up to the preovulatory stage in the presence or absence of 20 nM ATP (a similar concentration to that of medium-sized follicle fluid) were investigated. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…ATP levels in cumulus cells and follicular fluid could affect the quality of oocyte maturation, and normally high levels of ATP promoted oocyte development (Wakizoe et al, 2015; Yu et al, 2010). Treatment of MII stage oocytes with exogenous ATP (DMNPE‐caged ATP) was found to fail to improve the developmental rate of bovine SCNT blastocysts (Xue et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ATP levels in cumulus cells and follicular fluid could affect the quality of oocyte maturation, and normally high levels of ATP promoted oocyte development (Wakizoe et al, 2015; Yu et al, 2010). Treatment of MII stage oocytes with exogenous ATP (DMNPE‐caged ATP) was found to fail to improve the developmental rate of bovine SCNT blastocysts (Xue et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that with F I G U R E 1 BFF3 have a higher G0/G1 phase ratio and SWI/SNF complex gene expression after contact inhibition. ATP levels in cumulus cells and follicular fluid could affect the quality of oocyte maturation, and normally high levels of ATP promoted oocyte development (Wakizoe et al, 2015;Yu et al, 2010).…”
Section: Atp Content Affects the Expression Of Swi/snf Complex Genesmentioning
confidence: 99%